BANGLADESHI AND INDIAN YOUTH ATHLETES DIFFER IN STRENGTH AND ENDURANCE - Reza, Md Nasim; Rahman, Md. Hamidur; Andrabi, Syed Murtaza Hussain (International Journal of Research -GRANTHAALAYAH, 2022)
The purpose of the research was to investigate the health-related physical fitness of youth athletes from Bangladesh and India. The forty athletes from each country, Bangladesh (n=40) and India (n=40) were chosen using a simple random sampling method. The researchers selected Bangladeshi athletes from the Jashore district in Bangladesh and Indian athletes from the Murshidabad and Birbhum districts of West Bengal, India. Those who competed in at least one district-level competition were included in the study. For the study, the researchers chose male athletes between the ages of 17 and 21 years. The study included lower body explosive strength in the standing broad jump test, upper body muscular strength in the pull-up test and cardio-respiratory endurance in the cooper test as variables. The data was analysed using descriptive and inferential statistics (independent t-test), with the significance level set at 0.05. An independent sample t-test shows that Bangladeshi and Indian youth athletes standing broad jump t(78) = 2.10, sig. = 0.039; pull-ups t(78) = 1.68, sig. = 0.099; cooper test t(78) = 2.34, sig. = 0.022 respectively. The findings revealed a substantial difference in leg explosive strength and cardio-respiratory endurance, but no substantial difference in upper body muscular strength between Bangladeshi and Indian youth athletes.